Fuzzy logic based decision support for mass evacuations of cities prone to coastal or river floods. (November 2016) - Jia, Xiaojuan; Morel, Gilles; Martell-Flore, Hipolito; Hissel, François; Batoz, Jean-Louis
Abstract: Facing climate change and more frequent extreme weather conditions, coastal floods and inundations will become more severe. Evacuation can be an efficient solution to secure people's safety in a major disaster. The main difficulty in making an evacuation decision is the imprecise, incomplete and spatially varying nature of the crisis information. In this paper, a fuzzy-logic based method combined with Geographic Information System is proposed to analyze evacuation decision making scenarios. The method can handle qualitative and quantitative data at the same time, avoid sudden changes of decisions affected by uncertainties, and evaluate the spatial necessity to evacuate to support evacuation decision making. The method has been tested at the city of Bordeaux in France. The maps produced representing the need to evacuate can help decision makers better understand evacuation decision situation in terms of local impacts and crisis management anticipation. Highlights: A fuzzy-logic based method using spatial multicriteria analysis is proposed to analyze evacuation decision making scenarios. The method analyzes the spatial necessity to evacuate by integrating qualitative and quantitative data. The necessity to evacuate rate can avoid sudden changes of decisions affected by uncertainties. The evacuation necessity maps depicte local decision impacts and provide references for crisis management anticipation.